In silico Design and Molecular Docking Evaluation of Phenothiazine Derivatives as Selective Celecoxib Bound to S121P Murine COX-2 Inhibitors for Targeted Therapy of Inflammatory Bowel Disease - Dharam, Mayuri Girish; Bhor, Rohit Jaysing; Kolhe, Mahesh Hari; Bhoknal, Mayuri Rajesh; Jadhav, Pratibha Shankar (Asian Journal of Biological and Life Sciences, 2026)
Introduction: Inflammatory Bowel Disease (IBD), encompassing Crohn’s disease and ulcerative colitis, is a chronic inflammatory condition characterized by dysregulated immune responses and excessive production of pro-inflammatory mediators. Despite advancements in therapeutic strategies, current treatments are often associated with limitations such as adverse effects, high cost, and reduced long-term efficacy. Therefore, the identification of novel, safe, and effective therapeutic agents remains a significant challenge. Materials and Methods: In the present study, a series of phenothiazine-based derivatives (MD-1 to MD-12) were designed and evaluated using an integrated in silico approach. The crystal structure of Cyclooxygenase-2 (COX-2) (PDB ID: 5JW1) was selected as the target protein due to its critical role in mediating inflammatory responses. Molecular docking analysis was performed to assess the binding affinity and interaction patterns of the designed compounds within the active site of COX-2. Results: The docking results revealed that several derivatives, particularly MD-5, MD-6, MD-7, and MD-8, exhibited strong binding affinities with docking scores ranging from −10.0 to −10.4 kcal/mol, along with stable hydrogen bonding, electrostatic, and hydrophobic interactions. Furthermore, physicochemical properties, pharmacokinetic behavior, and drug-likeness of the compounds were evaluated using established computational tools. Most derivatives demonstrated favorable oral bioavailability, acceptable lipophilicity, optimal topological polar surface area, and compliance with Lipinski’s rule of five. ADME analysis indicated high gastrointestinal absorption and minimal blood-brain barrier permeability, suggesting reduced central nervous system side effects. Conclusion: These compounds may serve as potential lead molecules for further experimental validation and development of targeted therapies for IBD.
Keywords: ADME Analysis; Anti-inflammatory Agents; Cyclooxygenase-2 (COX-2); Inflammatory; Bowel Disease (IBD); Molecular Docking; Phenothiazine Derivatives; Structure-Based Drug; Design